2018
DOI: 10.3390/ijerph16010070
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Climate Change and Health Vulnerability and Adaptation in Dominica

Abstract: A climate change and health vulnerability and adaptation assessment was conducted in Dominica, a Caribbean small island developing state located in the Lesser Antilles. The assessment revealed that the country’s population is already experiencing many impacts on health and health systems from climate variability and change. Infectious diseases as well as food and waterborne diseases pose continued threats as climate change may exacerbate the related health risks. Threats to food security were also identified, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 17 publications
0
32
0
1
Order By: Relevance
“…Even still, the WHO assessment guidelines were useful in guiding methodology with regard to the selection of the geographic region, health outcomes of interest, participant selection, data collection methods and tools. While the application of VA assessment guidelines in this study is not its first use in the Caribbean [42], it is the first to focus on non-communicable diseases, providing support for the utility of the guidelines to research a variety of health outcomes. A limitation of this study is the involvement of only health professionals to understand the current and future vulnerabilities to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Even still, the WHO assessment guidelines were useful in guiding methodology with regard to the selection of the geographic region, health outcomes of interest, participant selection, data collection methods and tools. While the application of VA assessment guidelines in this study is not its first use in the Caribbean [42], it is the first to focus on non-communicable diseases, providing support for the utility of the guidelines to research a variety of health outcomes. A limitation of this study is the involvement of only health professionals to understand the current and future vulnerabilities to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…They may also have few climate and health models for application, low capacity within country teams to conduct the analysis, and limited financial resources and time to contract appropriate academic teams to conduct more sophisticated studies. Schnitter et al [60] reported that challenges encountered in completing a V&A in Dominica in 2015 included insufficient resources and expertise to undertake modeling of future health impacts for more than one issue (vector-borne diseases), limited health data for analysis, and challenges prioritizing adaptation options.…”
Section: Discussionmentioning
confidence: 99%
“…Households with a family member employed outside the camp will be high capacity. Household involved the emergency planning will be highly capacity (19) Data analysis…”
Section: Selection Of Indicators and Weights For Hazard Vulnerabilitmentioning
confidence: 99%
“…Capacity refers to the ability to react to and reduce the adverse effects of potential or experienced hazards. It includes both current community capacity to cope with the public health hazards (epidemic diseases) in camps and future action to improve the ability to prepare (19). Capacity adaptive to public health risks depends on several factors such as economic wealth, knowledge about disease transmission and prevention, institutions, availability of basic services, community engagement, and participation (20).…”
Section: Introductionmentioning
confidence: 99%